A experi??ncia religiosa de Yokaanam no contexto da sa??de mental: uma leitura fenomenol??gica - Vilela, Paula Rey (2015)
This research focuses on one person leader of a messianic movement in Brazil, Master Yokaanam, originally called de S?? Ocean. This was diagnosed with religious paranoia psychiatry. Nevertheless, Master Yokanaam effected a rich religious and community life. Question as it did his religious experience and their possible connections and distinctions with the mystic delirium, as proposed by traditional psychopathology. The aim was to describe their religious experience and critically examine their diagnosis, from an ethical point of view, epistemological and practical. It was considered for such discussions the knowledge of jasperiana psychopathology, Freudian psychoanalysis, psychology of religion, especially in William James, phenomenology of Husserl and Merleau-Ponty, and an introduction to Kantian philosophy. The method was the historiography and the history of life. We see that Yokaanam started its activities "psychic" in childhood, however, he only came to take them over in 1944 after the fall of President Vargas plane, which was official pilot. From this episode, he says he accepted his call to continue the Emmanuel Mission, becoming the Master Yokaanam, the Spiritual Head of the Religious Institution Universal Spiritual Brotherhood. His religious experience presents itself in the creation of eclectic doctrine in relief work for children abandoned in mediumship, the characters of belief reincarnated history and incorporation of Umbanda entities. From this, now has followers who sought him initially in search of spiritual healing. Without commenting on the ontological reality of the transcendent, the phenomenological approach adopted in this research led to glimpse such phenomena without delegitimizing Yokaanam experience with the transcendent, with time and space, as well as what happens in your world of life, the intentionality of consciousness. That is, a comprehensive clinic, their religious experiences are not just appreciated by its form or its contents, which resemble religious delusion, or the speeches of power that prevail in the West, they tend to dichotomizing human perceptions between false and true. Instead, they are seen as intrinsic to his own life story, and in this, their destination lived as prophetic, behaving fundamental sense in their context and with those who surround him.